2019
DOI: 10.3823/833
|View full text |Cite
|
Sign up to set email alerts
|

First data on antimicrobial susceptibility patterns of Moraxella catarrhalis isolates in Lebanon

Abstract: Background. Moraxella catarrhalis is an important bacterial pathogen. Although national data have shown an increase in the levels of antimicrobial resistance in clinical settings in Lebanon, there is a lack of data regarding this human pathogen. This study aimed to determine for the first time the antimicrobial susceptibility profiles of M. catarrhalis isolates in Lebanon. Methods. A total of 34 M. catarrhalis strains were isolated from clinical specimens during the period from November 2010 to March 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Previous studies have reported very high levels of resistance to erythromycin in M. catarrhalis isolates, for instance, 76.9% of isolates were resistant in Pakistan, 34 but in this study resistance to erythromycin was low. Resistance to ciprofloxacin was also moderate but significantly lower than previously reported in Lebanon (97.1%) 35 . The increase in the prevalence of quinolone‐ and macrolide‐resistant isolates may be due to their increased use for empirical treatment of common respiratory infections and non‐prescription use by the public in most low‐income countries such as Zambia.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Previous studies have reported very high levels of resistance to erythromycin in M. catarrhalis isolates, for instance, 76.9% of isolates were resistant in Pakistan, 34 but in this study resistance to erythromycin was low. Resistance to ciprofloxacin was also moderate but significantly lower than previously reported in Lebanon (97.1%) 35 . The increase in the prevalence of quinolone‐ and macrolide‐resistant isolates may be due to their increased use for empirical treatment of common respiratory infections and non‐prescription use by the public in most low‐income countries such as Zambia.…”
Section: Discussionmentioning
confidence: 65%
“…Resistance to ciprofloxacin was also moderate but significantly lower than previously reported in Lebanon (97.1%). 35 The increase in the prevalence of quinolone-and macrolide-resistant isolates may be due to their increased use for empirical treatment of common respiratory infections and nonprescription use by the public in most low-income countries such as Zambia.…”
Section: Discussionmentioning
confidence: 99%